2019
DOI: 10.1111/scs.12784
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle‐related risk factors among patients with coronary artery disease in Nepal

Abstract: Background Coronary artery disease (CAD) is the leading cause of death and morbidity globally. South Asia, including Nepal, has higher risks for CAD due to relatively higher exposures to risk factors. This study evaluated the prevalence of lifestyle‐related risk factors and the associations of risk factors with socio‐demographic variables among CAD patients. Methods A cross‐sectional study was conducted among CAD patients (n = 224) admitted to a national heart centre in Nepal. Data on dietary habits, smoking, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…By using standard questionnaires, information regarding eating habits, smoking, ethanol intake, perceived stress, physical activity, body weight, and compliance to therapeutic regimens was attained. Even though there was a high prevalence of self-reported risk factors within the study cohort, on this occasion, alcohol consumption was reported by only 23% of participants [57].…”
Section: Alcohol Consumption and Atherosclerotic Vascular Diseasementioning
confidence: 71%
“…By using standard questionnaires, information regarding eating habits, smoking, ethanol intake, perceived stress, physical activity, body weight, and compliance to therapeutic regimens was attained. Even though there was a high prevalence of self-reported risk factors within the study cohort, on this occasion, alcohol consumption was reported by only 23% of participants [57].…”
Section: Alcohol Consumption and Atherosclerotic Vascular Diseasementioning
confidence: 71%
“…Kadınların erkeklerle karşılaştırıldığı çalışmalarda diyabet, hipertansiyon, lipid düzeyleri, sigara kullanımı, kan basıncı değerleri, psikososyal durum ve fiziksel aktivite fark bulunmaktadır. [14,18,19] KAH için sigara önemli bir risk faktörüdür. Sigara kullanan bireylerde KAH başta olmak üzere bir çok kronik hastalık görülmektedir.…”
Section: Cinsiyetunclassified
“…Yapılan çalışmalarda KAH olan kadınların stres düzeyleri erkeklere göre daha yüksek bulunmuştur. [19,21] Bu çalışmaların aksine, bu araştırmada her iki cinsiyette stres algısı paralellik göstermektedir. Bunun sebebi her iki cinsiyettin sosyo-demografik ve hastalık özelliklerinin benzerlik göstermesi olabilir.…”
Section: Cinsiyetunclassified
“…The latest EUROASPIRE V survey has reported that the basic lifestyle habits are fundamental risk factors for cardiovascular disease that require more emphasis and focus (Kotseva et al., 2019 ; Mozaffarian et al., 2008 ). South Asian population have a higher prevalence of risk factor habits regardless of their residence in South Asia or otherwise (Ahmed et al., 2018 ; Gaudel et al., 2020 ; Ghimire & Dhungana, 2018 ; Khanal et al., 2018 ). Diet low in whole grains, vegetables and fruits, smoking, alcohol consumption and low physical activity are the lifestyle choices of people in Nepal which are leading risk factors for CAD, contributing to higher incidence of CAD and unacceptable numbers of premature deaths (Bhattarai et al., 2020 ; Ghimire & Dhungana, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The latest EUROASPIRE V survey has reported that the basic lifestyle habits are fundamental risk factors for cardiovascular disease that require more emphasis and focus (Kotseva et al, 2019;Mozaffarian et al, 2008). South Asian population have a higher prevalence of risk factor habits regardless of their residence in South Asia or otherwise (Ahmed et al, 2018;Gaudel et al, 2020;Ghimire & Dhungana, 2018;Khanal et al, 2018).…”
mentioning
confidence: 99%